TRANSLATION ASSESSMENT IN TRANSLATING IDIOM IN THE FILM WEDNESDAY (2022) - Sianturi, Christina Agatha; Pakpahan, Carolina; Golame, Javad (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
Translation assessment is the process of determining how successfull a translation from one language to another language. This study aims to assess the quality of idiom translation in Indonesian subtitles using the FAR (Functional Equivalence, Acceptability, Readability) model by Jan Pedersen (2017). This study employed a qualitative descriptive design using the documentation method. The data were obtained from the English dialogues and Indonesian subtitles of the Wednesday (2022) series. A data sheet was used to record and classify idiomatic expressions, while an assessment sheet based on Pedersen’s (2017) FAR Model, comprising Functional Equivalence, Acceptability, and Readability, was used to evaluate translation quality. The data were analyzed by identifying idioms, comparing their translations, and assessing the accuracy, naturalness, and readability of each subtitle according to Pedersen’s error classification scale. A total of 40 idiomatic expressions were identified and analyzed. The results show that in terms of Functional Equivalence, all the idioms were translated accurately. In terms of Acceptability, the translation is generally acceptable, but some still feel stiff due to a tendency towards literalness. In terms of Readability, the subtitles are generally easy to understand, although some parts pose readability challenges. Overall, the translation of idioms in this film's subtitles is quite good because it is able to convey the meaning, cultural nuances, and humor of the source text while maintaining acceptability and readability.